Perceived social distancing and hygienic practices in the restaurants during covid-19 pandemic: evaluation of restaurants’ future - Baskaya Sezer, Duygu; Daskin, Mustafa; Pala, Kenan; Asan, Kübra (Journal of Business on Hospitality and Tourism, 2022)
This study was carried out to examine the applicability of COVID-19 pandemic rules and measures and the future of the restaurant sector in a Turkish context. In this survey, a total number of 218 usable questionnaires were personally retrieved via online from the respondents in the research location. A quantitative approach was adopted in this study and SPSS version 23 was employed in order to explain the data. In general, the results show that the people are mostly careful of the rules and guidelines. Significantly, some respondents around 30% did not agree on some items such as SD4, SD2 and H25 which should be taken into account. Demographically, the result shows that the individuals with graduate degrees scored the items of the survey lower than the others. This paper provides implications for authorities in terms of minimizing the effect of pandemics and maximizing the hygienic practices among restaurant operators in future. Theoretically, the current study by examining the applicability of COVID-19 pandemic rules and measures lends further contribution to the related literature.